2007
DOI: 10.1038/sj.onc.1210172
|View full text |Cite
|
Sign up to set email alerts
|

A chemical biology approach identifies a beta-2 adrenergic receptor agonist that causes human tumor regression by blocking the Raf-1/Mek-1/Erk1/2 pathway

Abstract: A chemical biology approach identifies a beta 2 adrenergic receptor (b2AR) agonist ARA-211 (Pirbuterol), which causes apoptosis and human tumor regression in animal models. b2AR stimulation of cAMP formation and protein kinase A (PKA) activation leads to Raf-1 (but not B-Raf) kinase inactivation, inhibition of Mek-1 kinase and decreased phospho-extracellular signal-regulated kinase (Erk)1/2 levels. ARA-211 inhibition of the Raf/ Mek/Erk1/2 pathway is mediated by PKA and not exchange protein activated by cAMP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 45 publications
(47 reference statements)
9
64
3
3
Order By: Relevance
“…Carie and Sebti demonstrated that inhibition of the Raf-1/ Mek-1/ERK1/2 pathway by a β-AR agonist can result in growth inhibition of MDA-MB-231 breast cancer cells in vivo [26] . Shin et al reported that the catecholamines stimulate β2-AR while carcinogens like nicotine can interact with β2-AR to activate the downstream protein kinase C/ERK1/2/ cyclooxygenase 2 pathway, leading to the proliferation of gas- [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Carie and Sebti demonstrated that inhibition of the Raf-1/ Mek-1/ERK1/2 pathway by a β-AR agonist can result in growth inhibition of MDA-MB-231 breast cancer cells in vivo [26] . Shin et al reported that the catecholamines stimulate β2-AR while carcinogens like nicotine can interact with β2-AR to activate the downstream protein kinase C/ERK1/2/ cyclooxygenase 2 pathway, leading to the proliferation of gas- [27] .…”
Section: Discussionmentioning
confidence: 99%
“…A549 or H1650 cells were harvested and resuspended in PBS and implanted s.c. into the right and left flanks (10 Â 10 6 cells per flank) of 8-wk-old female athymic nude mice (Charles River) as described (18,23). When tumors reached f100 to 200 mm with ABC kit from Vector Laboratories, rinsed in dH 2 O, and developed with 3,3 ¶-diaminobenzidine.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Carie and Sebti have demonstrated that ADRB2 agonist pirbuterol causes human tumor regression in MDA-MB-231 breast cancer in vivo by blocking the Raf-1/Mek-1/Erk1/2 pathway. However, the authors acknowledge that this approach is limited to human cancers that not only express ADRB2, but also that stimulation of this receptor results in the blockade of the Raf-1/Mek-1/Erk 1/2 pathway [27]. In addition to the stimulation by catecholamines on ADRB2, carcinogens like nicotine may interact with ADRB2 and the downstream protein kinase C/Erk1/2/cyclooxygenase 2 pathway to lead to cell proliferation of gastric cancer cells [28].…”
Section: Proliferation and Growth Of Primary Tumor And Metastasesmentioning
confidence: 99%